RETRACTED ARTICLE: Functionalized graphene oxide nanosheets with folic acid and silk fibroin as a novel nanobiocomposite for biomedical applications - Reza Eivazzadeh-Keihan; Farkhondeh Alimirzaloo; Hooman Aghamirza Moghim Aliabadi; Ehsan Bahojb Noruzi; Ali Reza Akbarzadeh; Ali Maleki; Hamid Madanchi; Mohammad Mahdavi (Scientific Reports)
Abstract In this paper, a novel graphene oxide-folic acid/silk fibroin (GO-FA/SF) nanobiocomposite scaffold was designed and fabricated using affordable and non-toxic materials. The GO was synthesized using the hummer method, covalently functionalized with FA, and then easily conjugated with extracted SF via the freeze-drying process. For characterization of the scaffold, several techniques were employed: Fourier-transform infrared (FT-IR), field emission scanning electron microscopy (FE-SEM), energy dispersive X-ray (EDX), and thermogravimetric analysis (TGA). The cell viability method, hemolysis, and anti-biofilm assays were performed, exploring the biological capability of the nanobiocomposite. The cell viability percentages were 96.67, 96.35 and 97.23% for 24, 48, and 72 h, respectively, and its hemolytic effect was less than 10%. In addition, it was shown that this nanobiocomposite prevents the formation of Pseudomonas aeruginosa biofilm and has antibacterial activity.